2020
DOI: 10.1039/c9ta11784a
|View full text |Cite
|
Sign up to set email alerts
|

Establishing structure-sensitivity of ceria reducibility: real-time observations of surface-hydrogen interactions

Abstract: Unraveling the thermodynamic origin of the structure–reducibility of cerium oxide (100) and (111) surface planes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 55 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…All the latter LEED data let assume that the reduction of the ceria NPs in our work cannot be so high, eventually well below 50 %. Indeed, XPS shows that the efficiency of the H 2 reduction is quite low: when annealing the sample at 427 °C in 1.5 × 10 −6 mbar H 2 , about 20 hours are needed to obtain a 24 % large reduction [41]. A very recent micro X-Ray absorption spectroscopy (µXAS-PEEM) study shows that the degree of reduction remains low (CeO ∼1.9 ) if a stoichiometric CeO 2 (111) film is reduced by annealing at 550 °C during a dosage of 26 000 L of H 2 [70].…”
Section: Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All the latter LEED data let assume that the reduction of the ceria NPs in our work cannot be so high, eventually well below 50 %. Indeed, XPS shows that the efficiency of the H 2 reduction is quite low: when annealing the sample at 427 °C in 1.5 × 10 −6 mbar H 2 , about 20 hours are needed to obtain a 24 % large reduction [41]. A very recent micro X-Ray absorption spectroscopy (µXAS-PEEM) study shows that the degree of reduction remains low (CeO ∼1.9 ) if a stoichiometric CeO 2 (111) film is reduced by annealing at 550 °C during a dosage of 26 000 L of H 2 [70].…”
Section: Reductionmentioning
confidence: 99%
“…To study the role of a metal support that changes its state between being metallic and oxidized, the inverse ceria/Cu(111) catalyst is an ideal model surface [21,26]. The ceria/Cu(111) system has been extensively studied in the past [27], particularly by LEED [28,29,30,31,32,33,34,35,36,37], RHEED [38,15], LEEM [39,40,41], XPS [29,30,42,26,43,44,33,34,45,35,20,46,36,47,37,15,48,41] and by STM [30,32,26,49,33,34,45,35,46,36,47,37] as well as by density functional theory (DFT) [21,…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of the interaction between H 2 and ceria is crucial to understanding the mechanism of ceria catalyzed selective hydrogenation reactions [25][26][27][28][29]. Many studies have found that the homolytic dissociation of H 2 to form two hydroxyl (OH) groups is thermodynamically favored on the stoichiometric surface of ceria [6,30].…”
Section: Introductionmentioning
confidence: 99%
“…The processes that alter the surface structure and chemistry during operation are spatially heterogeneous in nature and thus require spatially nonaveraging techniques, 16 such as spectromicroscopy, to be captured in their entirety. However, while separate spectroscopic and microscopic studies are abundant, as discussed, a proper spectromicroscopical study is missing.…”
Section: ■ Introductionmentioning
confidence: 99%